Color-advertising strategies of invasive plants through the bee eye - Dessart, Martin; Aguiar, João Marcelo Robazzi Bignelli Valente; Tabacchi, Eric; Guillerme, Sylvie; Giurfa, Martin (Frontiers in Plant Science, 2024)
Invasive plants represent a significant global challenge as they compete with native plants for limited resources such as space, nutrients and pollinators. Here, we focused on four invasive species that are widely spread in the French Pyrenees, Buddleja davidii, Reynoutria japonica, Spiraea japonica and Impatiens glandulifera, and analyzed their visual advertisement signals with respect to those displayed by their surrounding native species using a perceptual approach based on the neural mechanisms of bee vision given that bees are regular pollinators of these plants. We collected 543 spectral reflections from the 4 invasive species, and 66 native species and estimated achromatic and chromatic similarities to the bee eye. R. japonica, S. japonica and B. davidii were inconspicuous against the foliage background and could be hardly discriminated in terms of color from their surrounding native plants.These characteristics promote generalization, potentially attracting pollinators foraging on similar native species. Two morphs of I. glandulifera were both highly salient in chromatic and achromatic terms and different from their surrounding native species. This distinctive identity facilitates detection and learning in association with rich nectar. While visual signals are not the only sensory cue accounting for invasive-plant success, our study reveals new elements for understanding biological invasion processes from the perspective of pollinator perceptual processes..